2001
DOI: 10.1034/j.1600-0714.2001.301002.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and immunohistochemical analysis of calcifying odontogenic cysts

Abstract: We conclude that COCs with various histological features have neoplastic potential and may not be separate entities within the same histological spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
11

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 21 publications
2
39
0
11
Order By: Relevance
“…In CCOT, cytokeratins 14 and 19 have been identified in the epithelial component, with CK6 expression in both the epithelium and ghost cells [38]. The proliferation fraction, as assessed by Ki-67, is very similar to ameloblastoma, particularly in those lesions where the lining is obviously ameloblastoma-like [39,40]. The solid lesions show a similar immunophenotype [41].…”
Section: Lesions Containing Ghost Cellsmentioning
confidence: 75%
“…In CCOT, cytokeratins 14 and 19 have been identified in the epithelial component, with CK6 expression in both the epithelium and ghost cells [38]. The proliferation fraction, as assessed by Ki-67, is very similar to ameloblastoma, particularly in those lesions where the lining is obviously ameloblastoma-like [39,40]. The solid lesions show a similar immunophenotype [41].…”
Section: Lesions Containing Ghost Cellsmentioning
confidence: 75%
“…It is clinically characterized as a painless-slow-growing tumor, that affects the maxilla as well as the mandible, and generally occurs in young adults in the third or fourth decade of life. It exhibits no sexual predilection and is most commonly seen in the anterior region [7] [8]. CCOT can present alone, as in the present case, or is associated with other odontogenic tumors, such as odontomas, adenomatoid odontogenic tumors, and ameloblastomas [9].…”
Section: Discussionmentioning
confidence: 90%
“…In the 8 cases, the patient age ranged from 5 to 45 years, with a mean age of The discussion about the neoplastic behavior of CCOT is still recent. Yoshida et al [7] The recommended treatment for CCOT is usually conservative and consists of enucleation with curettage, i.e., enucleation followed by removal of a 1 -2 mm layer of bone around the complete periphery of the cystic cavity with a sharp curette or a bone bur [13]. The purpose of this procedure is to remove epithelial debris that could turn into a recurrent lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Takata (10) found that the mean PCNA labeling index in the nonproliferative type was lower than that in the proliferative type, and that in the malignant COC was higher than in benign COC. Yoshida et al (16) also found that the mean Ki-67 labeling index was slightly greater in proliferative COC, combined COC or COC with ameloblastomatous proliferation than in those without these histological features, and that the proportion of cases positive for bcl-2 was slightly higher in COCs with odontoma than in those without odontoma.…”
Section: Discussionmentioning
confidence: 93%